COMO ABRIR MÃO DO PROFISSIONAL DE EDUCAÇÃO FÍSICA NA EDUCAÇÃO INFANTIL? - da Conceição de Souza, Jocilene; de Souza Cordeiro, Lilliany (LINKSCIENCEPLACE, 2026)
Physical education is very important in child development so it should be inserted for the child to recognize his body and the environment in which he lives. The development of the child through movement, action, experience and creativity so it is possible the formation of his conscience, expressing his feelings, thoughts, his spatial, temporal movement, color distinction, forms and acquired experiences, these can strengthen his relationship with the other with itself into reality .The Physical Education in preschool and in early elementary school grades operates in preventive nature. Through these many problems can be avoided such as difficulty in concentrating, confusion in word recognition, with letters, syllables and other literacy-related problems.